Assessment of Interleukin-19 Level and Factors Associated with Breast Cancer for A Sample of Al-Najaf Women, Iraq - Abbas, Ali Najeh; Hamid, Wasan Sami (Medical Science Journal for Advance Research, 2024)
Background: Among women, breast cancer is the primary cause of cancer-related mortality, with a 5-year survival rate after metastases of more than 20%. Therefore, improving early diagnosis is essential to improving the prognosis of the condition. The study aimed to assess Interleukin-19 (IL-19) as markers in women with breast cancer. Materials and methods: This study is case-control design was conducted at National Hospital for Oncology and Hematology in Najaf and AL-Sadder Medical City Hospital. A convenience sampling of 160 samples. The study comprised two groups include 80 patients with breast cancer, 80 healthy controls. Five millilitres of venous blood were collected from every individual in the study consecutively, the blood distributed into: gel tubes (6ml). Interleukin-19 (IL-19) were measured by ELISA kit, the biochemical kit used in the study for performed by a company Sun long Biotech Co, Ltd. Results: The results found that patients had significantly lower mean IL-19 levels (9.814±4.992 Pg/ml) than controls (33.666±11.49 Pg/ml), at statistically significant P. value <0.001. Also, the results found that there was no significant difference between stages (P. value >0.05). At the same time all stages (0-III) were gradually lower mean IL-19 levels compared to healthy controls (P. value <0.001). Conclusions: The present study found that Interleukin-19 level were lower significantly in women with breast cancer. Furthermore, the results reveal that patients with metastatic BC had significantly lower mean IL-19 levels compared controls.